Analisis Pengendalian Persediaan Bahan Baku Menggunakan Metode Economic Order Quantity (EOQ): Studi Kasus pada PT Maju Bersama Industri - Denny Andwiyan; Jawahir Jawahir; Patrick Andraes Napitupulu (Journal of Science, Technology, and Innovation, 2026)
Raw material inventory control is one of the crucial aspects in maintaining the continuity of production processes in manufacturing companies. Inaccuracy in determining the amount of raw material orders often causes two opposing problems, namely excess inventory (overstock), which results in increased storage costs, or inventory shortages (stockouts), which can disrupt the overall production process. This study aims to analyze raw material inventory control at PT Maju Bersama Industri by applying the Economic Order Quantity (EOQ) method as a quantitative approach to determine the most economical order quantity. The research method used is descriptive quantitative research with primary data obtained through direct interviews with the production manager and secondary data from the company’s inventory reports for one year. Based on the calculation results, the EOQ value obtained is 1,549 units per order, the optimal ordering frequency is 15 times per year, the total inventory cost is Rp7,745,967, the safety stock is 200 units, and the Reorder Point (ROP) is 600 units. The results of this study indicate that the consistent implementation of the EOQ method can help companies minimize total inventory costs while maintaining raw material availability so that production processes can run smoothly and efficiently.